ax-bx-ay+by
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 02:43:18
ax-bx-ay+byax-bx-ay+byax-bx-ay+byax-bx-ay+by=(ax-ay)-(bx-by)=a(x-y)-b(x-y)=(a-b)(x-y)=(ax-ay)-(bx-by
ax-bx-ay+by
ax-bx-ay+by
ax-bx-ay+by
ax-bx-ay+by
= (ax-ay) -(bx-by)
=a(x-y)-b(x-y)
=(a-b)(x-y)
=(ax-ay)-(bx-by)
=a(x-y)-b(x-y)
=(a-b)(x-y)
ax+by-ay-bx
ax-bx-ay+by
(ax+bx+ay+by)-(ax-bx-ay-by)化简
ax+ay+bx+by(因式分解)
ax-bx-ay+by 因式分解
ax-ay-bx+by因式分解
因式分解 (ax+by+ay)^2+(bx-ay)(ax+by+ay)+(bx-ay)^2
(AX+BY)平方+(BX-AY)平方
因式分解:(ax-by)^2+(ay+bx)^2
2ax+2ay-bx-by因式分解
(ax+by)^2+(bx-ay)^2因式分解
(ax+by)^2+(bx-ay)^2
将ay+ax-by-bx分解因式
(ax+by)^2-(ay+bx)^2
(ax+by)^2+(bx-ay)^2
(ax-by)²+(bx+ay)²
(ax+by)²+(ay-bx)²
ax+2bx+ay+2by能化简吗?